Editorial statement: The first two years of EJGE - Diego Varela; Giacomo Benedetto; Jose Manuel Sanchez-Santos (European Journal of Government and Economics (EJGE), 2013)
In this editorial statement we explain the developments in the European Journal of Government and Economics in its second year of existence. In this period, the journal has continued its international expansion, entered some new indices and started to experience its impact, as measured by the number of citations in other journals. After two years of publication, we have also learned some lessons that should help us redefine the role of EJGE.
Keywords: 330; Academic publishing; academic journal; internationalisation; indexing; academic impacten